Perancangan Sistem Manajemen Pemeliharaan Peralatan IT Berbasis Android - Febryan Hari Purwanto (Gayaku Publisher, 2024)
IT devices has become a primary requirement for most companies, agencies, universities and the business world. Dependency on IT equipment in operational processes requires well-managed care and maintenance. However, currently there is still a lot of equipment maintenance in companies or agencies that is only carried out if there is damage and is still recorded manually in logbook sheets which makes it difficult for technicians to see track records of maintenance and is less effective and takes time to make reports. In this research, an Android-based IT Equipment Maintenance Management System was designed. The Android application designed is able to help speed up the submission of repairs, maintenance actions as well as the time for creating maintenance reports and track records of IT equipment. Backend application is web-based using a MySql database with a server connected to the internet using a Static IP Public, so that it can be accessed from anywhere. Applications for users and technicians are made based on Android, making it easy to use anywhere and anytime. By using this application, equipment repair requests by users, equipment repair and maintenance actions by technicians and maintenance reports can be carried out quickly, efficiently and effectively.